Effects of Temperature, Particle Size and Enzyme Addition on Biogas Production In-Vitro - Lamichhane, Sanjaya; Rudd, Lars Erik (Journal of Agriculture and Forestry University, 2025)
Biogas is an anaerobically produced ecofriendly renewable form of energy which can address the harmful effects associated with conventional source of fossil fuels. The objectives of present study were to examine effects of temperature, particle size and enzymes on biogas production. Moose (Alces alces) thrives in woody browse in semi arctic region and it was presumed that it hosts unique micro-organisms capable of producing fibrolytic enzymes. An experiment was conducted in the laboratory of Inland Norway University, Blæstad. Cow manure with 5% dry matter content and wheat straw with 3 different particle size were treated with 3 dose of Moose rumen bacteria (MRB) culture along with 3 temperature settings. A cubical model was selected according to DoE (Design of experiments) and 11 treatments with different combinations of treatments were tested. 100ml Erlenmeyer flasks were used as reactors, whereas gas was collected in 100 mL syringes. The data were then analyzed using MODDE pro and MS Excel. The study shows that increase in temperature and enzyme has positive main effects and interaction effects for achieving a high rate of biogas production. The study reveals the positive effect of using of MRB culture on the production of biogas since it contains novel microorganisms able to promote biomass digestion.